Exploring Students’ Engineering Design Thinking in The Renewable Energy Topic: A Case of Problem Identification and Developing Ideas and Plans - Handayani, Rif’ati Dina; Lesmono, Albertus Djoko; Prastowo, Srihandono Budi; Supriadi, Bambang; Dewi, Nila Mutia; Azis, Kharisma Rafian; Thohir, Mohammad Anas (Jurnal Pendidikan Fisika Indonesia, 2024)
Science learning provides an opportunity to prepare students with 21st-century Engineering Design Thinking skills (EDT). EDT is a means of looking at and addressing daily real-world problems that greatly need solutions. This study aims to explore students’ EDT skills on alternative energy issues, specifically problem identification and developing ideas and plans. This research is a qualitative exploratory study in a senior high school in the Jember district. The learning design in this study uses the Science Learning through Engineering Design (SLED) models. Research data was gathered through observation and students’ worksheet documents. Content analysis is used as an approach to analyzing data. The results indicated that EDT trains students’ thinking processes to become more critical through problem identification and creativity in developing new ideas and imagination. EDT provides opportunities for students to combine their creativity and critical thinking to produce innovative design solutions. It improves students' epistemic comprehension while studying and helps them acquire relevant knowledge. This research is expected to be supplementary information for teachers to integrate EDT into their learning so that students can achieve meaningfulness and epistemic understanding.